Equipping New English Graduates for Professional Teaching Careers: A Strategic Preparation Program - Nurhasanah, Amalia; Pratama, Aryawira; Sumardi, Mayang Sastra; Sulman, Fauzan; Siregar, Suryana (AL-ISHLAH: Jurnal Pendidikan, 2024)
This research aims to explore the critical preparations necessary for fresh graduates to effectively engage in a professional teacher program, focusing on identifying specific challenges and enablers within this process. Employing a case study design, this research leverages qualitative interviews to capture in-depth perspectives from participants, enabling a nuanced exploration of the complexities involved in preparing for professional teacher programs. The research involved interviewing six professional teachers, including three who have participated in the in-service Professional Teacher Program (PPG) and three who have undergone the pre-service PPG. These teachers represent five different districts, which enhances the validity and generalizability of the findings. The selected participants are educators who have completed their professional teaching certification within the past three years, ensuring that the insights gained are current and relevant. The research identified six major themes: infrastructure challenges, health considerations, family support, technology mastery, financial constraints, and teacher qualifications. These themes emerged from the interviews and reflect the diverse experiences and obstacles faced by teachers in preparing for and undergoing professional development. This study provides actionable insights and can also inform the refinement of strategies for both preparation and development of targeted support systems for prospective teachers, which ultimately enhance the effectiveness of professional teacher programs for the present and the future. This study provides information that education with a well-planned and effective system can encourage better student quality and ability.